2019
DOI: 10.1158/1541-7786.mcr-18-1361
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation of CDH1 in Glioblastoma Cancer Stem Cells Attenuates APC/CCDH1 Activity and Pharmacologic Inhibition of APC/CCDH1/CDC20 Compromises Viability

Abstract: Glioblastoma (GBM) is the most common and lethal primary brain tumor and remains incurable. This is in part due to the cellular heterogeneity within these tumors, which includes a subpopulation of treatment-resistant cells called cancer stem-like cells (CSC). We previously identified that the anaphase-promoting complex/cylosome (APC/C), a key cell-cycle regulator and tumor suppressor, had attenuated ligase activity in CSCs. Here, we assessed the mechanism of reduced activity, as well as the efficacy of pharmac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Anaphase-Promoting Complex (APC/C) inhibitors, such as proTAME and apcin, targeted cell cycle proteins for proteasomal-mediated degradation. The targets of APC/C are regulated throughout the cell cycle via two mutually exclusive activator proteins, CDH1 and CDC20 [ 31 ]. W-13 is a calmodulin antagonist that could inhibit cell growth and induce cell apoptosis, which may display antitumor effects by binding to CAMK2G protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anaphase-Promoting Complex (APC/C) inhibitors, such as proTAME and apcin, targeted cell cycle proteins for proteasomal-mediated degradation. The targets of APC/C are regulated throughout the cell cycle via two mutually exclusive activator proteins, CDH1 and CDC20 [ 31 ]. W-13 is a calmodulin antagonist that could inhibit cell growth and induce cell apoptosis, which may display antitumor effects by binding to CAMK2G protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of proTAME on APC/C activity also seems to have great therapeutic potential. In combination with other inhibitors, proTAME was shown to be efficient in overcoming resistance caused by the hyperphosphorylation of CDH1 in glioblastoma cells [9], polo-like kinase 1 (PLK1)-based drug resistance in ovarian cancer cells [10] and CDC20-based resistance in diffuse large B-cell lymphoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…The binding site of Apcin on Cdc20 has been identified [ 19 ] and a study on SAR has revealed that the pyrimidine ring and aminal nitrogens, together with the hydrophobic trichloromethyl group, are important structural motifs; in contrast, the elimination of the nitro-imidazole moiety produces little effect. Apcin showed preclinical activity against multiple myeloma [ 26 ], prostate cancer [ 27 ], glioblastoma [ 28 ] and osteosarcoma [ 29 ] cells. Very recently, during the current investigation, the synthesis and the in vitro evaluation in a panel of solid tumor cells [MCF-7, A375, A549, HepG2, Hela, Ovcar-3 and Caov-3) of a series of 2,2,2-trichloro-1-aryl carbamate derivatives in which Apcin was modified by changing the pyrimidinyl or the 1-(2-methoxyethyl)-2-methyl-5-nitro-1H-imidazolyl moiety, has been reported [ 30 ].…”
Section: Resultsmentioning
confidence: 99%